PENGARUH STRUKTUR KEPEMILIKAN PERUSAHAAN TERHADAP TAX AVOIDANCE DI INDONESIA DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Marfiana, Andri; Andriyanto, Toto (Jurnal Pajak dan Keuangan Negara (PKN), 2021)
Tax avoidance is a strategy that companies can take to reduce their tax payments. The purpose of this study is to look at the effects of family, foreign, and government ownership on tax avoidance. This study also tries to identify the effect of corporate governance on tax avoidance by companies with family, foreign, and government ownership. Corporate governance is seen from the existence of multiple large shareholders (MLS), independent commissioners, and audit quality by BIG 4-affiliated public accounting firms. Tax avoidance is measured using the effective tax ratio (ETR) and book tax different (BTD). The population of this study is a company listed on the Indonesia Stock Exchange for the period 2017-2019. The research sample was selected using purposive sampling technique which resulted in 141 companies for analysis. The results of this study indicate that family, foreign, and government ownership have a positive effect on tax avoidance. The existence of MLS in companies with family and foreign ownership causes a negative effect on tax avoidance. The existence of auditors from KAP Big 4 does not reduce the possibility of companies with family, foreign and government ownership involved in tax avoidance practices. Meanwhile, the existence of independent commissioners does not have a significant effect on the relationship between family, foreign, and government ownership on tax avoidance.